The HuRaA trial - the radiocapitellar line shows significant posterior translation in healthy elbows: a prospective analysis of 53 healthy individuals - Schamberger, Christian T.; Großner, Tobias; Rehnitz, Christoph; Findeisen, Sebastian; Ferbert, Thomas; Höppchen, Arnold; Schmidmaier, Gerhard; Stein, Stephan (Biomedicines, 2024)
Background: The elbow joint is stabilized by complex interactions between bony structures and soft tissues, notably the lateral and medial collateral ligaments. Posterolateral rotatory instability (PLRI), a form of elbow instability, is challenging to diagnose due to overlapping symptoms with other conditions. The radiocapitellar line (RCL) is a radiographic tool for assessing humeroradial alignment and elbow stability, but its diagnostic accuracy remains debated. This study aims to provide normative data on RCL deviations in healthy individuals to improve diagnostic criteria for PLRI. Methods: A prospective study was conducted with 53 healthy individuals (27 males, 26 females) aged 18-45 years. MRI scans of the participants’ elbows were performed in maximum extension and supination to assess radiocapitellar deviations (RCDs). Two orthopedic surgeons independently analyzed the images to evaluate RCDs and assess interobserver reliability. Statistical analyses, including independent t-tests and Pearson correlations, were used to explore the relationship between RCDs, demographic factors, and elbow stability. Results: The average RCD in the cohort was 1.77 mm (SD 1.06 mm). Notably, 62.9% of participants had deviations greater than 1.2 mm, while 12.9% exceeded 3.4 mm, thresholds traditionally used to diagnose PLRI. Gender and age did not significantly influence RCD values. The interobserver reliability was almost good (ICC = 0.87), supporting the consistency of the RCL measurements. Conclusions: Significant RCDs occur even in asymptomatic individuals, challenging the current diagnostic thresholds for PLRI based solely on RCL measurements. A comprehensive assessment that includes clinical, anatomical, and functional evaluations is essential for accurate diagnosis. These findings highlight the need for refined diagnostic criteria and further research into elbow stability.
Gesehen am 17.04.2025